(untitled) (KYAMC Journal, 2024)
Background: Workplace violence (WPV) in healthcare settings is a significant global occupational and mental health concern, which is a major stressor for nurses, particularly in middle-income and low-income countries. It has serious negative consequences for the physical and mental well-being of healthcare workers and threatens the workplace environment for providing healthcare services. Objective: To determine the prevalence, risk factors, and perceived effects of workplace violence on nurses in a purposively selected medical college hospital situated in Dhaka, Bangladesh. Materials and Methods: A hospital-based cross-sectional study was initiated to determine the prevalence, risk factors, and perceived effects of workplace violence among the 220 nurses working in the Shaheed Suhrawardy Medical College Hospital. Results: Most of the nurses (50.5%) faced violence in their workplace, or outside of the workplace or both. Among them 45.9% faced violence in their workplace alone, 38.8% faced violence in both places and 15.3% faced violence on the way to their workplace in terms of violence outside the workplace alone. Regarding the type of WPV and violence outside the workplace (VOW), the majority of the nurses experienced psychological violence (93.6% and 81.7%, respectively). Nurses’ age, marital status, work experiences, and workplace distance from residence all had a statistically significant (p<0.05) relationship with their experience of violence. The sex of the nurses and the distance of their workplace from their residence were similarly statistically significant (p<0.05) about the place of occurrence of the incident. In addition, Nurses’ age and marital status were statistically related (p<0.05) to different types of workplace violence. Conclusion: Workplace violence has a negative impact on both the health and productivity of nurses. Workplace regulations and protocols focusing on safety in the workplace, reporting and surveillance, and education for all employees and management on how to avoid and handle violence are required. The hospital administration has also prioritized initiatives to minimize violence. KYAMC Journal Volume: 14, No: 03, October 2023: 120-129.